The future of common agricultural policy and the challenges of Europe 2020 strategy - Andreea Dragoi; Cristina Balgar (Global Economic Observer)
Currently, the Common Agricultural Policy (CAP) faces a series of challenges involving the need for strategic decisions for the long term future of European agriculture and rural areas in the European Union. To be effective in addressing these challenges, the CAP must work within a framework of connected economic policies and sustainable public finances that contribute to accomplish the EU. In this context, it should be noted that the Europe 2020 Strategy revealed a new perspective for the CAP reform, the main development directions being focused on finding the most appropriate solutions to the new economic, social and environmental issues brought on by the international economic crisis, also contributing to the sustainable development of EU agriculture. In what follows, we will briefly review the existing proposals at EU level for future development directions of the CAP.